Repeatable Battery for the Assessment of Neuropsychological Status (RBANS): preliminary utility in adult neuro-oncology. Issue 4 (8th December 2018) - Loughan, Ashlee R; Braun, Sarah E; Lanoye, Autumn
Abstract: Background: Neurocognitive assessments have become integral to comprehensive neuro-oncology care. Existing screening tools may be insensitive to cognitive changes caused by medical treatments. Research supports the clinical value and psychometric properties of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) in various medical populations; however, there is minimal evidence for its use in neuro-oncology. The purpose of the current study was to further explore the cognitive profile of patients with primary brain tumor (PBT) using the RBANS and to assess rates of below-expectation performance compared to normative data and estimated intellectual functioning. Methods: Data were collected on 82 PBT patients (54% male; age range, 19-81 years). All patients were administered the RBANS-Update and the Advanced Clinical Solutions–Test of Premorbid Functioning (TOPF) according to standardized instructions. Cognitive strengths and weaknesses were identified for PBT patients. Descriptive analyses, t tests, and chi-squared tests were utilized to identify and compare cognitive profiles. Results: Overall, cognitive performance was low average for PBT patients. When compared to standardization data, PBT patients performed significantly worse across all 5 RBANS indexes, with Attention and Memory showing the largest discrepancies. Estimated intelligence analyses reflected greater deficits in cognitive functioning than when compared to a normal distribution. Conclusions: Preliminary research demonstrates the RBANS is an efficient screening tool to assess cognitive deficits in PBT patients. Data also support the importance of comparison to self, rather than normative distribution in ensuring proper identification and classification of patients.